Clovamide, a Hydroxycinnamic Acid Amide, Is a Resistance Factor Against Phytophthora spp. in Theobroma cacao - Knollenberg, Benjamin J.; Li, Guo-Xing; Lambert, Joshua D.; Maximova, Siela N.; Guiltinan, Mark J. (Frontiers in Plant Science, 2020)
The hydroxycinnamic acid amides (HCAAs) are a diverse group of plant specialized phenylpropanoid metabolites distributed widely in the plant kingdom and are known to be involved in tolerance to abiotic and biotic stress. The HCAA clovamide is reported in a small number of distantly related species. To explore the contribution of specialized metabolites to disease resistance in cacao (Theobroma cacao L., chocolate tree), we performed untargeted metabolomics using liquid chromatography – tandem mass spectrometry (LC-MS/MS) and compared the basal metabolite profiles in leaves of two cacao genotypes with contrasting levels of susceptibility to Phytophthora spp. Leaves of the tolerant genotype ‘Scavina 6’ were found to accumulate dramatically higher levels of clovamide and several other HCAAs compared to the susceptible ‘Imperial College Selection 1’ (‘ICS1’). Clovamide was the most abundant metabolite in ‘Scavina 6’ leaf extracts based on MS signal, and was up to 58-fold higher in ‘Scavina 6’ than in ‘ICS1’. In vitro assays demonstrated that clovamide inhibits growth of three pathogens of cacao in the genus Phytophthora, is a substrate for cacao polyphenol oxidase, and is a contributor to enzymatic browning. Furthermore, clovamide inhibited proteinase and pectinase in vitro, activities associated with defense in plant-pathogen interactions. Fruit epidermal peels from both genotypes contained substantial amounts of clovamide, but two sulfated HCAAs were present at high abundance exclusively in ‘Scavina 6’ suggesting a potential functional role of these compounds. The potential to breed cacao with increased HCAAs for improved agricultural performance is discussed.